Saúde no telejornal : a função pedagógica do telejornalismo nas séries especiais da TV Cabo Branco - Carneiro, Bruna Raquel Couto de Farias (2024)
This research aims to discuss the pedagogical function of television journalism observed in reports addressing health-related topics. In the context of contemporaneity, where various means of communication can be easily used for the dissemination of information from various areas, the importance of television as a medium for the transmission of news with an educational character becomes evident, which can result in good practices. The present study starts from the hypothesis that such contents can generate specific knowledge capable of positively impacting society in the field of health, through the use of didactic devices, initially raised by authors like Cerqueira (2018). To achieve this, the analysis proposes the examination of two series of special reports from TV Cabo Branco, a Globo affiliate in Paraíba, produced by journalists and healthcare professionals, focusing on issues related to human well-being. The method used is content analysis, anchored in bibliographic research and semi-structured interviews with professionals who were part of the analyzed television productions. The results obtained from this analysis point to the existence of various didactic devices, such as detailing, reinforcement in the discourse of legitimacy, interpretation of expert speeches, among others, in the reports of the analyzed series. In conclusion, the hypotheses initially raised and extensively discussed using theoretical resources in the chapters preceding the analysis are thus confirmed.